1992-2011 sea ice thickness estimation in the Ross and Weddell Seas from SSM/I brightness temperatures - Aulicino, G.; Fusco, G.; Kern, S.; Budillon, G. (2013)
In polar regions, ocean-atmosphere interactions are strongly influenced by sea ice and its thickness. Obtaining the Antarctic sea ice thickness distribution is however still a challenge. This new Snow Ice Thickness estimation procedure (SIT) combines Special Sensor Microwave Imager (SSM/I) brightness temperatures in an empirical approach to obtain sea ice thickness in the Ross and Weddell Seas for seasonal ice up to a thickness of 2 m during freezing conditions. Retrievals are in good agreement with National Ice Center (NIC) ice charts and Antarctic Sea ice Process & Climate (ASPeCt) observations. Differently from the dramatic evidences in the Arctic and in the west Antarctic Peninsula, no negative trends can be detected in the studied regions over the considered 1992-2011 period.